B17 Characterisation Of A Huntington's Disease Cellular Model For The Transcriptome-based Expression Analysis Of Deubiquitinating Enzymes. (17th September 2014) - Rauen, M; Christensen, K; Thirstrup, K; Dantuma, N; Nørremølle, A; Dächsel, J; Fog, K
Abstract : Background: Huntington's disease (HD) displays a characteristic accumulation of mutant huntingtin (Htt) into cellular aggregates. Deficiency in protein clearance has been suggested as one of the mechanisms behind these accumulations and as such hypothesised to play a main contributing role in disease pathology and progression. The clearance of impaired or misfolded proteins is mostly accomplished through proteasomal and autophagosomal degradation. Proteins are tagged for degradation through ubiquitination, a dynamic process which involves among others deubiquitinating enzymes (DUBs). Interfering with the activity of this enzyme class represents a compelling tool for enhancing cellular clearance pathways and may thus present a novel therapeutic approach for the treatment of HD. Aims: Firstly, we strive to characterise a cellular model of HD with regards to mutant Htt aggregation and concomitant cytotoxic effects. Furthermore, the focus is laid on identifying DUBs which are expressed within this model Methods/techniques: The study is based on a cellular model of HD developed in the laboratory of Nico Dantuma. We used two PC12 cell lines expressing inducibly the first exon of human Htt harbouring either a pathogenic polyQ stretch of 94Q or a wild-type polyQ stretch of 16Q. In addition, Htt proteins were tagged with cyan fluorescent protein (CFP) at their C terminus. We characterised the model using immunohistochemical-based methods, fluorescent microscopy, as well as a cell viability assay. In order to investigate the DUB expression pattern RNA samples were extracted and subjected to cDNA conversion with subsequent whole transcriptome shotgun sequencing. Result/outcome: Analysis of the PC12 cell lines revealed a stable expression of the transgenes two days post induction of gene expression. Formation of aggregates was observed two days later in cells expressing HttCFP(94Q) whereas the wild-type variant of the Htt protein remained equally distributed throughout the cytoplasm. Additionally, cells expressing mutant Htt for four days demonstrated significantly higher cytotoxicity compared to cells expressing HttCFP(16Q). Cytotoxic effects increased over the next days. Based on these findings, it was concluded to collect RNA samples for subsequent whole transcriptome shotgun sequencing four days after induction of gene expression. Conclusions: Characterisation of the cellular HD model depicted robust and reproducible phenotypes and confirmed the use of these cell lines in order to investigate the landscape of DUBs and in the future to study the functional consequence of modulating these enzymes.